Unidirectionally progressive resection of left upper pulmonary lobe under video-assisted thoracoscopy - Cai, Kaican; Zhao, Hancheng; Wu, Hua; Feng, Siyang; Ren, Pengfei; Cai, Ruijun; Xiong, Gang (Journal of Thoracic Disease, 2014)
The case is a nodule in the upper left lobe, and intraoperative frozen section pathological diagnosis on the removed nodule confirmed well differentiated mucinous adenocarcinoma. Unidirectionally progressive resection of the left upper pulmonary lobe under video-assisted thoracoscopy is selected as the surgical method. Right below the operation hole, surgeons gradually advanced in one direction, and dissociated and divided in such order: the upper left pulmonary vein, the upper left lobe bronchus, the upper left pulmonary arterial branches and the fissures. Endoscopic linear cutters and hem-o-lok clip applicator were used to deal with the blood vessels, bronchus, and under-differentiated fissures. At last, the removed upper left lobe was put into a size eight sterile glove and taken out through the main operation hole. General anesthesia with double-lumen endotracheal intubation is used. The patient took a 90 degree decubitus on his contralateral side. The surgeons were on the ventral side of the patient, and operated with endoscope apparatus under the monitor.